2018
DOI: 10.1016/j.seppur.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Chromium removal from drinking water by redox-assisted coagulation: Chemical versus electrocoagulation

Abstract: Chemical Coagulation (CC) and Electrocoagulation (EC) processes using iron as coagulating agent were compared while treating aquifer water contaminated by a relatively high concentration of total chromium (CrT =19.0 mg L-1). A continuous semipilot comprising of EC (or CC), followed by flocculation, sedimentation and sandfiltration steps was used to remove CrT from water in order to get drinking water. A ratio of Fe/CrT ≥ 3 was required to reach the best efficiency of treatment using EC and CC. More than 99% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 19 publications
(13 reference statements)
0
23
0
Order By: Relevance
“…It has been well documented that EC technology is able to remove as much as 95-99% of various pollutants within a relatively short treatment time (Gao et al, 2010;Ricordel et al, 2014;Hashim et al, 2017b;Nariyan et al, 2018). It has been successfully used to purify water of pathogens (Ricordel et al, 2014), strontium (Nur et al, 2017), heavy metals (Hashim et al, 2017c;Martín-Domínguez et al, 2018), phosphate (Behbahani et al, 2011;Attour et al, 2014), and organic matter (Vepsäläinen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that EC technology is able to remove as much as 95-99% of various pollutants within a relatively short treatment time (Gao et al, 2010;Ricordel et al, 2014;Hashim et al, 2017b;Nariyan et al, 2018). It has been successfully used to purify water of pathogens (Ricordel et al, 2014), strontium (Nur et al, 2017), heavy metals (Hashim et al, 2017c;Martín-Domínguez et al, 2018), phosphate (Behbahani et al, 2011;Attour et al, 2014), and organic matter (Vepsäläinen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The maximum permissible limit for chromium content in drinking water recommended by the World Health Organization (WHO) is 0.05 ppm. Chemical precipitation [2], electrochemical reduction and coagulation [3], membrane separation [4], ion exchange [5,6] and adsorption [7,8] are used for removing chromium from wastewater. Among these methods, adsorption is effective for the chromium removal [9].…”
Section: Introductionmentioning
confidence: 99%
“…Chromium is a heavy metal that must be treated and removed in wastewater, and there are several articles that treat this metal in different ways and different treatment methods. For example, this article [18] made a comparison between coagulation and electrocoagulation using iron to treat the water contained in the aquifer contaminated by a relatively high concentration of total chromium. The results showed that more than 99% of (Cr) was eliminated by the Coagulation and Electrocoagulation methods.…”
Section: Related Workmentioning
confidence: 99%